2015
DOI: 10.1089/met.2014.0119
|View full text |Cite
|
Sign up to set email alerts
|

Urine 8-Isoprostane in Relation to Adiposity and Insulin Resistance in Individuals at High Cardiometabolic Risk

Abstract: Central obesity was independently associated with oxidative stress even in a population homogeneous for adiposity and cardiometabolic risk, whereas no relationship was observed between oxidative stress and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…When adjusting for it, however, the impact of oxidative stress marker on IR incidence was still evident. MetS, and waist circumference (originating in its components), most manifestly affected the development of IR, as corroborated by other investigators [15][16][17]. After adjustment for BMI, or waist circumference, no relationships plasma F2-isoprostanes with HOMA-IR were reported in longitudinal Park et al study, while in the other a cross-sectional study, relationship of urine 8-iso-PGF 2α was established as BMI-independent with regard to HOMA-IR only, although not with regard to IR [15,21].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When adjusting for it, however, the impact of oxidative stress marker on IR incidence was still evident. MetS, and waist circumference (originating in its components), most manifestly affected the development of IR, as corroborated by other investigators [15][16][17]. After adjustment for BMI, or waist circumference, no relationships plasma F2-isoprostanes with HOMA-IR were reported in longitudinal Park et al study, while in the other a cross-sectional study, relationship of urine 8-iso-PGF 2α was established as BMI-independent with regard to HOMA-IR only, although not with regard to IR [15,21].…”
Section: Discussionsupporting
confidence: 77%
“…Published data on oxidative stress in humans in relation to IR remain scarce and inconclusive. Some cross-sectional studies had demonstrated in humans a positive association between urine 8-iso-PGF 2α and IR, even though no such relationships were corroborated by other studies [15][16][17].…”
mentioning
confidence: 90%
“…The most representative vitamins in wholegrain are the B complex vitamins, ranging from one mg (for thiamin) to 11 mg (for nicotinic acid) in every 100 g of wholegrain; vitamin E is also present in a good quantity (two-to-seven mg/100 g wholegrain). Vitamin B complex may contribute to the regulation of hepatic glucose uptake [ 92 ], while vitamin E may be beneficial in reducing the oxidative stress and chronic low-grade inflammation associated with obesity, metabolic syndrome, and insulin resistance [ 93 , 94 , 95 ]. With respect to minerals, wholegrain is a good source of iron, magnesium, zinc, manganese, and selenium [ 72 ].…”
Section: Plausible Mechanisms By Which Wholegrains Might Protect Amentioning
confidence: 99%
“…10 Some published literatures have suggested that elevated 8-iso-PGF 2α was associated with obesity and fat accumulation. 11,12 To better achieve the early prevention of obesityrelated diseases, further understanding on the relationship between adiposity and lipid peroxidation is necessary. Ohmori et al 13 found that the levels of plasma 8-iso-PGF 2α were significantly higher in the high BMI group.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Some published literatures have suggested that elevated 8-iso-PGF 2α was associated with obesity and fat accumulation. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%